2017
DOI: 10.1111/cge.13064
|View full text |Cite
|
Sign up to set email alerts
|

Novel 9 amino acid in‐frame deletion in the NTRK1 tyrosine kinase domain in a patient with congenital insensitivity to pain with anhydrosis

Abstract: Schematic presentation of NTRK1 protein structure. Variants identified in this study are shown in red and previously reported variants associated with CIPA are shown in black (LRM, leucine rich motif; Ig, immunoglobulin-like domain; TM, transmembrane domain; TK, tyrosine kinase domain).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…They are also produced as a result of the increasingly employed CRISPR/CAS9 technology for genome editing [15]. Indels which are multiples of three nucleotides will maintain the open reading frame of genes but result in shorter/longer amino acid strands potentially altering the structure and function of proteins [16]. Indels which are not a multiple of three nucleotides give rise to frameshift mutations, thereby coding for an entirely different set of amino acids or resulting in a premature stop codon [17].…”
Section: Introductionmentioning
confidence: 99%
“…They are also produced as a result of the increasingly employed CRISPR/CAS9 technology for genome editing [15]. Indels which are multiples of three nucleotides will maintain the open reading frame of genes but result in shorter/longer amino acid strands potentially altering the structure and function of proteins [16]. Indels which are not a multiple of three nucleotides give rise to frameshift mutations, thereby coding for an entirely different set of amino acids or resulting in a premature stop codon [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no clear correlation between the genotype and phenotype of CIPA patients (2,19). Among 128 different mutations, we found that only four reports about gross deletion mutations (2,(20)(21)(22)(23); the largest deletion range was about 1,403 bp, which included exon5-6 (Supplementary Table 3). It affects the extracellular domain (2).…”
Section: Discussionmentioning
confidence: 96%
“…Patients with CIPA have mutations in NTRK1, the gene encoding TrkA, that affect TrkA expression and/or activity. Because mutations are found widely throughout the gene, symptoms vary from severe to mild and may include mental retardation, self-mutilation, multiple fractures, and developmental delay (14)(15)(16)(17)(18)(19). Few studies have biochemically characterized the mutations found in CIPA (19).…”
Section: Introductionmentioning
confidence: 99%
“…CIPA is a rare autosomal recessive disease characterized by loss of algesia and an inability to sweat. The worldwide incidence of CIPA is about 1 in 125,000,000 ( 14 , 15 ). Patients with CIPA have mutations in NTRK1 , the gene encoding TrkA, that affect TrkA expression and/or activity.…”
Section: Introductionmentioning
confidence: 99%